2016
DOI: 10.1016/j.yjmcc.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII-dependent phosphorylation of RyR2 promotes targetable pathological RyR2 conformational shift

Abstract: Diastolic calcium (Ca) leak via cardiac ryanodine receptors (RyR2) can cause arrhythmias and heart failure (HF). Ca/calmodulin (CaM)-dependent kinase II (CaMKII) is upregulated and more active in HF, promoting RyR2-mediated Ca leak by RyR2-Ser2814 phosphorylation. Here, we tested a mechanistic hypothesis that RyR2 phosphorylation by CaMKII increases Ca leak by promoting a pathological RyR2 conformation with reduced CaM affinity. Acute CaMKII activation in wild-type RyR2, and phosphomimetic RyR2-S2814D (vs. non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(86 citation statements)
references
References 56 publications
1
79
0
Order By: Relevance
“…The dysregulation of RyR that promotes this leaky state of the channel is not only associated with disease causing mutations in RyR, but also altered post-translational modifications that have been implicated in altering binding of RyR stabilizers, CaM and FKBP12/12.6 (1,3,4,6,1012). Moreover, excessive post-translational modifications are typically thought as key players in late-stage pathology.…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of RyR that promotes this leaky state of the channel is not only associated with disease causing mutations in RyR, but also altered post-translational modifications that have been implicated in altering binding of RyR stabilizers, CaM and FKBP12/12.6 (1,3,4,6,1012). Moreover, excessive post-translational modifications are typically thought as key players in late-stage pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Increased intracellular Ca 2+ levels suggest Ca 2+ overload in MO fetal cardiomyocytes, which may be associated with impaired activity of the Ca 2+ -release channel. Studies have shown that phosphorylation by PKA of RyR2 at Ser 2808 and phosphorylation by CaMKII of RyR2 at Ser 2814 can reduce the stability of the Ca 2+ release channel RyR2 and lead to a Ca 2+ leak from the SR associated with cardiac contractility dysfunction and heart failure (70)(71)(72)(73)(74). Our data show increased activity of PKA and CaMKII and high phosphorylation levels at both Ser 2808 and Ser 2814 of RyR2, which further confirm impaired contractile function in MO fetal cardiomyocytes at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac myocytes were isolated from New Zealand white rabbits and C57BL6 mice using retrograde Langendorff perfusion using Liberase TM (0.075 mg/mL, Roche) and Trypsin (0.0138%, Gibco) (37°C) as previously described [26]. All procedures were approved by the University of California Davis Institutional Animal Care and Use Committee (IACUC) in accordance with the NIH Guide for the Care and Use of Laboratory Animals.…”
Section: Methodsmentioning
confidence: 99%